c‐Myb promotes growth and metastasis of colorectal cancer through c‐fos‐induced epithelial‐mesenchymal transition - Qu, Xiao (Cancer Sci, 2019)
c‐Myb is a crucial transcription factor that participates in various biological functions; however, its role in colorectal cancer (CRC) remains poorly investigated. We first analyzed the expression and clinical significance of c‐Myb in a retrospective cohort enrolling 132 CRC patients. Then, the CRISPR/Cas9 technique was used to establish c‐Myb gene KO CRC cell lines. Cellular functional assays in vitro and in vivo were used to evaluate the impact of c‐Myb KO in CRC cells. Finally, RNA sequencing was used to investigate the potential oncogenic mechanisms regulated by c‐Myb in CRC progression and related cellular validations were accordingly carried out. As a result, c‐Myb is significantly overexpressed in CRC tissues as compared with adjacent normal tissues. High expression of c‐Myb is positively correlated with lymph node metastasis and poor prognosis. Univariate analysis and multivariate analysis further identify c‐Myb as an independent unfavorable prognostic factor for CRC patients. c‐Myb KO inhibits the proliferation, apoptosis resistance, invasion, metastasis, colony formation and in vivo tumorigenesis of CRC cells. Also, the mechanism investigation indicates that c‐Myb may promote CRC progression by regulating c‐fos. c‐fos overexpression can rescue the inhibitory effect of c‐Myb KO on the malignant characteristics of CRC cells. Finally, we find that c‐Myb KO inhibits the epithelial‐mesenchymal transition (EMT) molecular phenotype in CRC cells, whereas c‐fos overexpression can rescue this inhibitory effect. This study suggests that c‐Myb promotes the malignant progression of CRC through c‐fos‐induced EMT and has the potential to be a promising prognostic biomarker and therapeutic target.